A methodological framework to assess the employment impacts of transport infrastructure construction (Construction Economics and Building, 2025)
The aim of this study was to suggest a methodological evaluation framework for assessing the employment impacts of transport infrastructure construction. The applicability and usability of different ex-ante employment impact assessment methods were evaluated. Commonly, the employment impacts during construction are used as a justification for investment decisions. In this study, we tested three commonly used methods to estimate the employment impacts during the construction of three real-life case studies and compared the results to the known impacts of these projects. The results indicate that transport infrastructure construction is not an effective means of employment policy nationwide. This is partly due to insufficient labor supply in the infrastructure engineering and construction industries. A higher employment rate on a national level would require an increase in labor supply instead of an increase in labor demand. However, even though the national net impact on employment was close to zero, the gross regional impact on employment would still be useful information in project planning. The methodological framework, presented in this paper, helps to manage the employment impacts of transport infrastructure construction in a proper context.